Nonsmall Cell Lung Carcinoma with Giant Cell Features Expressing Programmed Death-Ligand 1: A Report of a Patient Successfully Treated with Pembrolizumab - Shingo Nakayama; Mamoru Sasaki; Shojiroh Morinaga; Naoto Minematsu (Case Reports in Oncological Medicine)
Giant cell carcinoma, a rare variant of nonsmall cell lung carcinoma (NSCLC), is characterized by aggressive progression and poor response to conventional chemotherapy. This report is the first to describe a patient with NSCLC and giant cell features who was successfully treated with pembrolizumab, an antibody targeting programmed death-1 (PD-1). A 69-year-old woman was diagnosed with NSCLC with multiple brain metastases. Histological evaluation of lung biopsy specimens revealed proliferation of pleomorphic giant tumor cells with poor cohesiveness, findings consistent with giant cell carcinoma. Immunostaining showed that a high proportion of the tumor cells were positive for expression of programmed death-ligand 1 (PD-L1). The patient received stereotactic radiotherapy for the brain metastases, followed by administration of pembrolizumab. Treatment with pembrolizumab resulted in the rapid regression of the primary lung nodule, with the progression-free period maintained for at least four treatment cycles. Immunotherapy targeting PD-1/PD-L1 may be an option for patients with PD-L1-positive NSCLC with giant cell features.